A handbook of methods for the study of adolescent children - Greulich, William Walter [...et all]. 1899- (Washington, DC : Society for Research in Child Development, National Research Council, 1966)
"This Handbook has been prepared as a methodological aid for students of child growth and development and for others who are concerned with the diagnosis, treatment, guidance and education of children, with particular reference to the period of adolescence. The material has been organized by disciplines, e.g., anatomy and anthropometry, physiology and biochemistry, pediatrics, psychology, etc., in accordance with the customary procedure, but the various methods and techniques have been grouped in the index according to the organ systems and functions to which they apply. The appearance of this Handbook may be viewed as an indication of the increasing interest in the study of child growth and development and of the realization that the various life sciences, especially the medical sciences, offer many valuable instruments for such study. In gathering the material for this Handbook, the guiding principle has been to select from the literature those methods, techniques, and procedures which might be employed to record and, if possible, measure the growing child, in order to reveal the rate and direction of growth and development, or the developmental sequence, of the various structures, functions, and activities that are being observed. In this endeavor, the study has been based upon the operational concept that, if instrumentally reliable measurements were made, they would yield valuable data on the growth process in man. The foregoing statement of some of the aims, purposes and methodological principles of the study of child development may serve to explain more fully the purpose and intent of this Handbook, since obviously a mere collection of methods and techniques can have little or no significance, apart from the problem or problems for which they are to serve as instruments. The methods outlined in the several sections of this Handbook are offered as instruments for the study of child growth and development with a full realization that the contributions from many important fields have been omitted because of limitations of personnel and time and that the methods included in this Handbook represent various methodological principles that are not in harmony"--Introduction. (PsycINFO Database Record (c) 2007 APA, all rights reserved)
Keywords: Adolescence; Child study; Growth; Adolescents; Child Psychology -- methods